Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea) - Podenas, Sigitas; Byun, Hye-Woo (Zootaxa, 2018)
The Korean species of Libnotes (Laosa) Edwards, 1926 and L. (Libnotes) Westwood, 1876 from Jeju Island are taxonomically revised. L. (Laosa) charmosyne (Alexander, 1958) and L. (Libnotes) divaricata (Alexander, 1924) are new records for South Korea and L. (Libnotes) byersiana n. sp. is described. An identification key for all Korean Libnotes, redescriptions and illustrations of the three currently known Jeju species are presented.